2014
DOI: 10.1155/2014/301485
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Self-Reported Questionnaire (KOOS) with Some Objective Measures in Primary OA Knee Patients

Abstract: Purpose. Objective of the present study was to see the correlation of subjectively measured KOOS questionnaire with objectively measured 6-minute walk test (6-MWT), age, height, weight, and BMI. Participants. 251 subjects with OA knee based on American College of Rheumatology criteria. Methods. After passing inclusion and exclusion criteria, the following parameters were recorded: age, height, weight, and BMI. Then subjects were asked to fill KOOS questionnaire; then all subjects were asked to do self-paced wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
6
2
Order By: Relevance
“…Similar to the results of our study, Sivachidambaram et al [14] correlated self-reported questionnaire (KOOS) with some objective measures in primary OA knee patients and found that KOOS has almost no correlation with age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the results of our study, Sivachidambaram et al [14] correlated self-reported questionnaire (KOOS) with some objective measures in primary OA knee patients and found that KOOS has almost no correlation with age.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Sivachidambaram et al [14] correlated selfreported questionnaire (KOOS) with some objective measures in primary OA knee patients and found that all KOOS subtypes have a significant correlation with 6-MWT. 6-MWT had a weak correlation with KOOS-ADL (=0.461) and a strong correlation with KOOS symptom, KOOS-pain, and KOOSsports (=0.578, 0.619, and 0.536, respectively) and a very strong correlation with KOOS-quality of life (=0.733) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, many patient-reported measurement tools are available for evaluating knee-related disabilities and postoperation quality of life. One patient-reported outcome tool is the Knee injury and Osteoarthritis Outcome Score (KOOS) measurement tool that provides subjective information about the disease process without examiner bias [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative and final follow-up Lysholm Knee Score (LKS), International Knee Documentation Committee (IKDC) score, Tegner Activity Scale (TAS) score, and Knee Injury and Osteoarthritis Outcome Score (KOOS) were used for functional evaluation between longitudinal and bucket-handle tears. [14][15][16][17]…”
Section: Clinical and Radiological Evaluationmentioning
confidence: 99%